Navigating the infodemic: strategies and policies for promoting health literacy and effective communication - Saleem, Sheikh Mohd; Jan, Shah Sumaya (Frontiers in Public Health, 2024)
The COVID-19 pandemic, with its vast impact illustrated by 770 million confirmed cases and 6.9 million deaths as of September 21, 2023, has exposed a critical challenge: the infodemic. Effective communication and health literacy are pivotal in addressing this crisis. This article emphasizes the urgency of combating health misinformation, highlighting its tangible impact on public health and social well-being. Trustworthy sources, especially government agencies and public health officials, played a central role in shaping public behavior. Clear, accurate, and consistent messaging became vital. Health literacy, a fundamental determinant of pandemic response, empowered individuals to understand and act upon health information. Approximately 36% of adults exhibited basic or below-basic health literacy skills, emphasizing its crucial role. Improving health literacy emerged as a strategic imperative, enabling informed choices and proactive health protection. The pandemic underscores the vital role of effective communication and health literacy in combating health misinformation, fostering informed decision-making, and safeguarding public health.